Kejadian bayi berat lahir rendah dan status gizi balita - Novika Kumala Dewi; Hesty Widyasih; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2015)
The nutritional status of Yogyakarta Province in 2010 was the high prevalence of childhood malnutrition. The highest malnutrition rate among children under five years old in Yogyakarta City was Gedongtengen Health Center amount of 15.88%. The greatest incidence of protein-energy malnutrition (PEM) among children in Sub Pringgokusuman at 17.46% and 10.74% the highest incidence of low birth weight (LBW) was also in Sub Pringgokusuman in 2010. The objective of this study is to determine the relationship of the incidence of LBW with the nutritional status of children in the Sub Pringgokusuman Region of Yogyakarta in 2012. Methods used Analytic observational with the case-control approach. The research was done in Sub Pringgokusuman. The population in this research was all children under five years old who had recorded on weighing in Sub Pringgokusuman. The samples in this research were childrenwho meet the inclusion criteria of children aged 12-59 months who experience abnormal nutrition and living with parents. Researchers took the whole case, with 40 cases and 40 controls. Source of data used primary data to the data by measuring the nutritional status of children's weight and height, as well as secondary data to see the history ofLBW with KMS Card. The result showed there is a relationship between the incidence ofLBWwith the nutritional status of children, there was a significant association with p-value is 9.5 x10-4. The proportion of abnormal nutrition events in children who have a history of low birth weight by 81%, theproportion of abnormal nutrition events in children who did not have a history of low birth weight by 39%, and the risk of LBW history for malnutrition among children under five years old had 6.49 times higher than children who did not have a history of LBW (95% Cl:1.813 to 29.913). The conclusion is that there is a relationship between the incidence ofLBW with the nutritional status of children, children with a history of low birth weight at risk for malnutrition as much as 6.49 times compared to children who did not have a history of LBW.